2000
DOI: 10.1002/1099-0488(20001015)38:20<2634::aid-polb30>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Branching effects on the segmental dynamics of polyethylene melts

Abstract: 13C NMR spin–lattice relaxation time and nuclear Overhauser effect measurements are reported for linear polyethylene, polyethylene with long branches, and linear polyethylene with infrequent short branches at 75 MHz over the temperature range of 400–535 K. A quantitative description of the segmental dynamics of the main‐chain methylene units and the branch points is obtained for linear polyethylene with ethyl branches. At 400 K, the correlation time is 29 ps for the segmental dynamics of the branch point but 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Its rheological properties are of considerable practical importance to optimize processing conditions, and numerous dynamic studies of polyethylene melts have been reported. Experimental rheological 1−5 and NMR 6,8,7 measurements have been particularly informative and have been supplemented by computer simulations. 9−21 Systematic investigations have been carried out to understand the rheological behavior as a function of temperature and molar mass, M, and to test molecular theories of polymer melt dynamics, specifically the Rouse and reptation models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its rheological properties are of considerable practical importance to optimize processing conditions, and numerous dynamic studies of polyethylene melts have been reported. Experimental rheological 1−5 and NMR 6,8,7 measurements have been particularly informative and have been supplemented by computer simulations. 9−21 Systematic investigations have been carried out to understand the rheological behavior as a function of temperature and molar mass, M, and to test molecular theories of polymer melt dynamics, specifically the Rouse and reptation models.…”
Section: Introductionmentioning
confidence: 99%
“…Its rheological properties are of considerable practical importance to optimize processing conditions, and numerous dynamic studies of polyethylene melts have been reported. Experimental rheological and NMR ,, measurements have been particularly informative and have been supplemented by computer simulations. …”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics and molecular mechanics calculations show that inclusion of short branches such as −CH 3 and −CH 2 CH 3 dramatically increases the intermolecular interaction between adjacent chains. 27,28 This allows the pressure created by conformational changes during creation, propagation, and annihilation of dynamic defects to be efficiently distributed to adjacent chains, allowing the entire crystal lattice respond homogeneously to local conformational stress. Therefore, given sufficient time, and assuming a high concentration of branches, the average conformational space spanned by the C−D vectors at D 2 and D 4 positions will be equivalent, leading to a homogeneous distribution of oscillation amplitudes observed in PE15 and PE21.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…[10] Studies of polyethylene-copolymers containing comonomers of different lengths have previously shown that the various branch lengths impart different local segmental mobility. [11] With nuclear relaxation phenomena sensitive to local segmental mobility, resulting from the dominant heteronculear dipolar coupling relaxation pathway, [12] they may be used to probe changes in branch length. The effect of comonomer length on 13 C spin-lattice relaxation time (T C 1 ) has been investigated in both the solution-state [13] and the melt-state.…”
Section: Full Papermentioning
confidence: 99%